Molecular Probe Crossing Blood–Brain Barrier for Bimodal Imaging–Guided Photothermal/Photodynamic Therapies of Intracranial Glioblastoma. (7th February 2020) - Li, Bo; Xiao, Hong; Cai, Mingyue; Li, Xiaoxia; Xu, Xiaolin; Wang, Shiyin; Huang, Si; Wang, Yong; Cheng, Du; Pang, Pengfei; Shan, Hong; Shuai, Xintao
Abstract: Currently, treatment of intracranial diseases still remains a great challenge because the blood–brain barrier (BBB) blocks access of most drugs to the central nervous system. Herein, a theranostic small molecular probe, iRGD‐ICG‐Lys‐DTPA@Gd (iRGD‐ILD), capable of crossing BBB is developed. Owing to the small molecular size and αv β3 integrin receptor–mediated transcytosis, this tailor‐made molecular probe integrating the fluorescence and magnetic resonance imaging functions effectively passes through BBB to target tumor cells even in the early stage of glioblastoma multiforme (GBM), thereby allowing a bimodal imaging–guided therapy of GBM. The reactive oxygen species and heat generated by the ICG moiety under the 808 nm laser irradiation exert photodynamic/photothermal therapeutic effects, which results in significantly inhibited tumor growth and prolonged median survival of C6‐Luc glioma‐bearing mice. Notably, the integration of FDA‐approved clinically available agents, e.g., ICG, DTPA and Gd, into a molecular probe may ensure desirable biocompatibility and biosafety for in vivo applications. Overall, the results highlight the potential of a water‐soluble small molecule as a novel theranostic probe for highly effective GBM treatment. Abstract : A theranostic molecular probe capable of crossing the blood–brain barrier is developed. The tailor‐made molecular probe, integrating fluorescence and magnetic resonance imaging functions, allows bimodal imaging–guided effective therapy of intracranial glioblastoma even in the early stage.